Gambaran Pengetahuan Ibu Tentang Karies Pada Anak Kelas A TK Dharma Wanita Panjunan Sidoarjo - Rahma Aprilia Ahmadi Putri; Silvia Prasetyowati; Ida Chairanna Mahirawatie (Poltekkes Kemenkes Surabaya, 2024)
Introduction: Dental caries is one of the dental and oral health problems that is often experienced by Indonesian people. The 2018 Riskesdas stated that 78% of the group of children aged 3-5 years experienced problems with oral and dental health, the most common being dental caries, meaning that only 22% of the group of children aged 3-5 years were free from dental caries. Problem: The problem in this study is the high average value of def-t in class A children at Dharma Wanita Kindergarten Panjunan Sidoarjo.The Purpose: The aim of the study was to describe the mother's knowledge about dental caries in class A children at Dharma Wanita Kindergarten Panjunan Sidoarjo. Methods: This research is a descriptive study involving 41 respondents. This research data was collected using a questionnaire sheet. The data analysis technique is by calculating the average answer which is calculated on the average (mean) and presented and then presented in tabular form. Results: Based on the research results, it was found that the mother's knowledge about the causes of dental caries was in the sufficient category, the mother's knowledge about the consequences of dental caries was in the sufficient category, the mother's knowledge about how to prevent dental caries was in less category, and the mother's knowledge about treating dental caries was in less category. Conclusion: Mother's knowledge about dental caries in class A children at Dharma Wanita Panjunan Sidoarjo Kindergarten was obtained in the sufficient category.